Middle-Aged and Older African Americans' Information Use During the COVID-19 Pandemic: An Interview Study - Tang, Lu; York, Felicia N.; Zou, Wenxue (Frontiers in Public Health, 2021)
African Americans in the United States have been disproportionately affected by the COVID-19 pandemic in infection and mortality rates. This study examined how middle-aged and older African American individuals accessed and evaluated the information about COVID-19. Semi-structured interviews with 20 individuals (age: 41–72) were conducted during the first stay-at-home advisory period in late March and early April 2020. The phronetic iterative approach was used for data analysis. We found that these individuals primarily relied on information scanning based on their routine media consumption to acquire information about COVID-19 and seldom actively searched for information outside of their regular media use. Individuals used several strategies to assess the quality of the information they received, including checking source credibility, comparing multiple sources, fact-checking, and praying. These findings could inform media and governmental agencies' future health communication efforts to disseminate information about the COVID-19 pandemic and future infectious disease outbreaks among the African American communities.